Allergy Modulation by N-3 Long Chain Polyunsaturated Fatty Acids and Fat Soluble Nutrients of the Mediterranean Diet - Hogenkamp, Astrid; Ehlers, Anna M.; Garssen, Johan; Willemsen, Linette (Frontiers in Pharmacology, 2020)
The Mediterranean diet, containing valuable nutrients like n-3 long chain poly-unsaturated fatty acids (LCPUFAs) and other fat-soluble micronutrients, is known for its health promoting and anti-inflammatory effects. Its valuable elements might help in the battle against the rising prevalence of non-communicable diseases (NCD) including the development of allergic diseases and other (chronic)inflammatory diseases. The fat fraction of the Mediterranean diet contains bioactive fatty acids but can serve as a matrix to dissolve and increase the uptake of fat-soluble vitamins and phytochemicals like luteolin, quercetin, resveratrol and lycopene with known immunomodulatory and anti-inflammatory capacities as well. Especially n-3 LCPUFAs like eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) derived from marine oils can target specific receptors or signaling cascades, act as eicosanoid precursors and/or alter membrane fluidity and lipid raft formation hereby exhibiting anti-inflammatory properties. Beyond n-3 LCPUFAs, fat-soluble vitamins A, D, E and K1/2 have the potential to affect pro-inflammatory signaling cascades by interacting with receptors or activating/inhibiting signaling proteins or phosphorylation in immune cells (DCs, T-cells, mast cells) involved in allergic sensitization or the elicitation/effector phase of allergic reactions. Moreover, fat-soluble plant-derived phytochemicals can manipulate signaling cascades, mostly by interacting with other receptors or signaling proteins compared to those modified by fat-soluble vitamins, suggesting potential additive or synergistic actions by applying a combination of these nutrients which are all part of the regular Mediterranean diet. Research concerning the effects of phytochemicals such as polyphenols has been hampered due to their poor bio-availability. However, their solubility and uptake are improved by applying within the dietary fat matrix. Alternatively, they can be prepared for targeted delivery by means of pharmaceutical approaches like encapsulation within liposomes or even unique nanoparticles. This review illuminates the molecular mechanisms of action and possible immunomodulatory effects of n-3 LCPUFAs and fat-soluble micronutrients from the Mediterranean diet in allergic disease development and allergic inflammation. This will enable us to further appreciate how to make use of the beneficial effects of n-3 LCPUFAs, fat-soluble vitamins and a selection of phytochemicals as active biological components in allergy prevention and/or symptom reduction.